El efecto de la inoculacion con micorrizas sobre la nutricion fosforica de la yuca - Howeler, Reinhardt H. (International Center for Tropical Agriculture, 1980)
The effect of inoculating cassava with mycorrhizae on plant growth and P uptake was studied in sterilized and nonsterilized soils to which 8 levels of P were applied, as well as in a flowing culture solution at 4 different P concn. Inoculation produced greater than benefits in cassava grown in sterilized soil when 2 t P/ha were applied, increasing DM production almost 3 times and the total absorption of P some 7 times. In nonsterilized soil, both the production of DM and P uptake increased 50 percent when 0.5 t P/ha were applied. In the soil expt, cassava presented mycorrhizal infection only with intermediate rates of P application (0.1-4 t/ha), corresponding to a concn of 2-52 microM of P in soil solution. With no P and with the 2 highest P rates (8 and 16 t/ha), inoculation with mycorrhizae had no beneficial effects and the percentage of infection was low, especially in the nonsterilized soil. In the flowing culture solution inoculation significantly increased DM production of 8 cassava cv. with the intermediate concn of 1 microM P, whereas there was no effect on maize, rice, common beans and cowpeas. These crops produced max yields at 1 microM P, while cassava required at least 10 microM P. With concn of 10 and 100 microM P, the roots of inoculated cassava plants did not present mycorrhizal infection whereas with a low concn of 0.1 microM P, roots showed a high infection but this had no significant effect on yields. Some of the implications of the apparent dependency between cassava and mycorrhizae are discussed. (AS-CIAT)